Systems of equations in differentials with generalised derivatives of continuous functions - Анастасия Игоревна Жук; Елена Николаевна Защук (Журнал Белорусского государственного университета: Математика, информатика)
Herein, we investigate systems of nonautonomous differential equations with generalised coefficients using the algebra of new generalised functions. We consider a system of nonautonomous differential equations with generalized coefficients as a system of equations in differentials in the algebra of new generalised functions. The solution of such a system is a new generalised function. It is shown that the different interpretations of the solutions of the given systems can be described by a unique approach of the algebra of new generalised functions. In this paper, for the first time in the literature, we describe associated solutions of the system of nonautonomous differential equations with continuous generalized coefficients in the space L(T).